(untitled) (Scientia Agropecuaria, 2022)
Phytophthora capsici is an oomycete that causes various symptoms, such as root, neck, stem, fruit rot, and leaf blight, in different plant species, including the genus Capsicum. One of the tools to counteract this biotic problem, which may be more profitable and respectful to the environment in the long term, is using biocontrollers such as Bacillus, Pseudomonas, Streptomyces (bacteria), and Trichoderma (fungus). It seems that each of these microorganisms has different mechanisms that allow them to inhibit and reduce the growth of P. capsici, negatively affecting the development of sporangia, germination and motility of zoospores, and expansion of germ tube. Although this direct biocontrol action on the phytopathogen correlates with the reduction of symptoms in Capsicum plants or other plant species, this would also involve the activation of defense responses in plants against P. capsici induced by microorganisms. The activity of several enzymes related to the isoflavonoid pathways and reactive oxygen species, as well as the expression of different genes that encode proteins related to pathogenesis and other proteins that can activate the jasmonic acid, salicylic acid, or ethylene signaling pathways. Despite the few existing works related to the biochemical and molecular interaction of Capsicum–P. capsici–biocontroller, in this review, we outlined and elucidated the possible effects and metabolic pathways related to this tripartite pathosystem.